KESENIAN SENJANG DALAM HEGEMONI KEKUASAAN - Sukma, Irawan (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Hegemony in art was very obvious in the era of New Order. The government under the New Order regime had absolute power and was believed to be the strongest and could always direct everything including art. Hegemony in Art is packed heavily in traditional intelectualt bales believed to be social expressions. This too is the case with the Senjang arts in the Musi Banyuasin district experiencing the hegemony power from before freedom even to the present era of the Reformation. This proved that every performance of the Senjang poem was ever included by propaganda sentences of particular interest to those who resort to Senjang arts service. The study qualitative methods with the interpretation and cultural approach analysis and therefore the qualitative data in which researchers are the principal instruments of data collection. The source of the data that was targeted was the visual presentation of the Senjang and the audio recording of the Senjang in the grain. Furthermore, ethnographic methods are also used with emic and ethical approaches to finding the real problem.